A study of the stored energy in titanium under deformation and failure using infrared data - A.Yu. Fedorova; M.V. Bannikov; O.A. Plekhov (Fracture and Structural Integrity)
The work is devoted to the experimental study of heat dissipation caused by plastic deformation and failure processes taking place in a titanium alloy Ti-4.2Al-1.6Mn. To investigate the spatial and time evolution of temperature, a set of experiments has been carried out on plane titanium smooth specimens and specimens with pre-grown centered fatigue cracks. The original mathematical algorithm for experimental data processing has been applied to obtain the rate of heat dissipation generated by plastic deformation and stored energy. It is shown that the stored energy is accumulated in titanium specimens undergoing fatigue tests, and at the time of damage to fracture transition it is equal to zero